Kinematics prior to contact in landings preceded by rotation - Munkasy, B. A.; McNitt-Gray, J. L.; Welch, M. D. (1996)
The purpose of this study was to examine mechanisms gymnasts use to prepare for landings preceded by forward and backward rotation. These results indicate that landing forward rotation skills pose a different challenge and may require a different landing strategy than do drop landings and back saltos. To overcome these differences and the lack of success associated with forward rotation skills landing drills may need to be emphasized.